An ancient origin of the naked grains of maize - Regina A. Fairbanks; Jeffrey Ross-Ibarra (Proceedings of the National Academy of Sciences, 2025)
Adaptation to novel environments requires genetic variation, but whether adaptation typically acts upon preexisting genetic variation or must wait for new mutations remains a fundamental question in evolutionary biology. Selection during domestication has been long used as a model to understand evolutionary processes, providing information not only on the phenotypes selected but also, in many cases, an understanding of the causal loci. For each of the causal loci that have been identified in maize, the selected allele can be found segregating in natural populations, consistent with their origin as standing genetic variation. The sole exception to this pattern is the well-characterized domestication locus tga1 ( teosinte glume architecture1 ), which has long been thought to be an example of selection on a de novo mutation. Here, we use a large dataset of maize and teosinte genomes to reconstruct the origin and evolutionary history of tga1 . We first estimated the age of tga1-maize using a genealogy-based method, finding that the allele arose approximately 42,000 to 49,000 y ago, predating the beginning of maize domestication. We also identify tga1-maize in teosinte populations, indicating that the allele can survive in the wild. Finally, we compare observed patterns of haplotype structure and mutational age distributions near tga1 with simulations, finding that patterns near tga1 in maize better resemble those generated under simulated selective sweeps on standing variation. These multiple lines of evidence suggest that maize domestication likely drew upon standing genetic variation at tga1 and cement the importance of standing variation in driving adaptation during domestication.